A Communication Model of Art Information Accessibility for People with Disabilities - Navickaitė, Rugilė (Vilnius University Open Series, 2022)
People with disabilities still face barriers to participation in society, face freedom of choice, lack of opportunities to act independently, discrimination, accessibility issues, and equal rights. Only the physical accessibility of the environment is emphasized, but social activity is strongly influenced by the availability of information. Access to culture/art is physical and informational. Cultural organisations should integrate marketing tools into their activities through the communication process and the presentation of art products and services.Scientific problem – What integrated marketing communication tools do increase the information accessibility of art for people with disabilities?The object of the work is integrated marketing communication tools that increase the information accessibility of art for people with disabilities. The aim of the work is to develop an empirically based theoretical model of integrated marketing communication tools that increase the information accessibility of art for people with disabilities.
Keywords: Art; communication; access to information; people with disabilities; communication tools